Assessor efficiency and effectiveness using marking and feedback support systems - Wood, Lincoln (IADIS Press, 2012)
Pressures on Higher Education institutions include the need to improve marking and feedback support systems for students while carefully managing costs. Many approaches have been suggested, including the improved use of technology to reduce workload and help provide richer feedback to students. In this research two marking and feedback support systems (MFSSs) are evaluated in an educational experiment. Each assignment was assessed by two markers, using two MFSSs (comparing Spreadsheets and the tsAAM software tool); where half the assignments were marked withone MFSS and the other half with the other MFSS. This enables comparisons of outcomes using different MFSSs while not disadvantaging any student. Neither of the MFSSs enabled faster marking and feedback provision; however. the tsAAM tool allowed the markers to provide significantly more feedback to the students in the same amount of time.